Constriction ring dystocia - Kaye, Christopher H. (1974)
A case of constriction ring dystocia in a 40-year-old multiparous white woman is described. She was postmature; the fetus occupied an unstable lie for which no cause could be demonstrated clinically or radiologically; during the course of an inert labour every third fetal heart sound was abnormal. At cesarean section it appeared that no lower uterine segment had formed and extreme thickness of the myometrium was encountered.